2016
DOI: 10.1007/s11606-016-3848-2
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Recovery to Pre-Fracture Function in Older Persons with Hip Fracture: an Observational Study

Abstract: Recovery rates are low, even among those with higher levels of pre-fracture functional status, and are worse for patients who are older, cognitively impaired, and who have multiple comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
76
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 21 publications
5
76
0
2
Order By: Relevance
“…As to this secondary analysis, we must mention the exclusion of 28 patients, either due to death/acute care readmission or missing data. However, these patients presented lower SDC and higher comorbidity on admission and overall worse outcome, thus suggesting that their exclusion was not a substantial bias to our final results, that are in line with some [9, 27], but not all studies focusing on HF recovery [25, 26, 32, 33]. Indeed, we must also point out that our model, although significant, explained only 24% of the variance of the final outcome; as we already acknowledged, the lack of information on the first stages of care and on surgery (timing, type) is the main limitation of our study, and, probably, our model would have been empowered by including this information [24, 27].…”
Section: Discussionsupporting
confidence: 82%
“…As to this secondary analysis, we must mention the exclusion of 28 patients, either due to death/acute care readmission or missing data. However, these patients presented lower SDC and higher comorbidity on admission and overall worse outcome, thus suggesting that their exclusion was not a substantial bias to our final results, that are in line with some [9, 27], but not all studies focusing on HF recovery [25, 26, 32, 33]. Indeed, we must also point out that our model, although significant, explained only 24% of the variance of the final outcome; as we already acknowledged, the lack of information on the first stages of care and on surgery (timing, type) is the main limitation of our study, and, probably, our model would have been empowered by including this information [24, 27].…”
Section: Discussionsupporting
confidence: 82%
“…Due to the high rates of cognitive impairment in this population and the association of cognitive impairment with poor functional recovery after surgical insults in older adults, the likelihood of undergoing a breast cancer surgery and having it impact a frail, elderly woman’s function in the long-term is plausible and likely. 15 …”
Section: Discussionmentioning
confidence: 99%
“…The finding of improvement in mobility measures, specifically climbing stairs and walking two blocks, between 3-and 6-month follow-up is particularly important when considering that prior studies in functionally heterogeneous populations demonstrated no significant change in function. 7,37 This finding highlights the need for additional investigation to the postoperative rehabilitation course, to ascertain those factors that may optimize the ability for recovery of mobility independence.…”
Section: Discussionmentioning
confidence: 96%